Quantitative trait loci underlying drought tolerance in the (brb 191 x seq 1027) f5 recombinant inbred line population of common bean (Phaseolus vulgaris l.) in Uganda - Nabateregga, Mabel (Makerere University, 2017)
The common bean (Phaseolus Vulgaris L.) is the most important food legume crop for direct consumption in the world. The crop is a primary protein source in the diet of many low-income populations globally. However, drought has become a major constraint affecting over 60% of dry bean production worldwide causing crop failure, hunger and poverty especially in Uganda. Development of drought tolerant cultivars is the most effective control measure in mitigating effects of drought on dry bean production. Significant research efforts have been made over the past two decades to improve common bean adaptation to drought. Consequentially, sources of drought tolerance have been identified; however, the genetic diversity and mechanistic behavior of drought tolerance within the common bean is still not fully understood. Drought tolerance is a physiologically complex process integrating several mechanisms and quantitative traits, which has made breeding for drought tolerance in the common bean very problematic. Furthermore, evaluation for drought tolerance is very laborious, time consuming and employs destructive sampling, which has further slowed efforts of improving the common bean. Therefore, marker assisted selection using genetic markers that are tightly linked to quantitative trait loci (QTL) controlling drought tolerance traits is the most feasible solution. The aim of this study was to identify phenotypic traits and quantitative trait loci underlying drought tolerance in the common bean. More specifically this research study aimed at (i) identifying key phenotypic traits and sources of drought tolerance in the intra-gene pool Andean cross (BRB 191 x SEQ 1027) population, (ii) Mapping QTL controlling drought tolerance in the genome and markers flanking these QTLs. The BRB 191 x SEQ 1027 population derived from drought tolerant lines BRB 191 and SEQ 1027 was evaluated for two years and I year under field and greenhouse conditions respectively at Kawanda in Uganda. The F5 RIL population comprising of 128 lines was assessed under drought stress (DS) and non-stress (NS) environments for twenty (20) drought related traits which included agronomic, morphological, phenological, and physiological components. Viable sources of drought tolerance were identified in the (BRB 191 x SEQ 1027), namely: lines114, 117, 91 and 41. Also, BRB 191 was affirmed as a viable source of drought tolerance. Drought stress in the field significantly affected all measured traits except harvest index (HI) and stem biomass reduction (SBR) (P˂0.001). However, chlorophyll content (SCMR), canopy temperature (CT), stem biomass reduction (SBR) and 100 seed weight (100SW) remained significantly stable under season by genotype by environment (Sn. Gen. E) interactions and genotype by environment (G x E) interactions as well (P˂0.001). Stability of these traits highlighted their usefulness in selecting for drought tolerance across different environments. Furthermore, pod partitioning index (PPI), harvest index (HI), chlorophyll content (SCMR) and stem biomass reduction (SBR) remained significantly stable under G x E effects. Significant correlations (P˂0.001) were also maintained between HI and PPI with seed yield under drought stress for 2 years in the field indicating the viability of photosynthate remobilization in increasing yield potential under drought stress conditions. A linkage map spanning 204.7 cM with an average distance of 3.4 cM between marker intervals was constructed using 60 single nucleotide polymorphic (SNP) markers in this study. Inclusive composite interval mapping (ICIM) revealed thirty six (36) major QTL from field (29 qtl) and greenhouse (9 qtl) evaluations (LOD≥3.0). Co-localization and clustering of a large number of QTL was detected on pv02 at 4 major chromosome positions. A major seed yield QTL SY2.1BS on pv02 was tightly linked to five major QTL associated with pod partitioning and phenology. Pleiotropy was also detected in the greenhouse between leaf biomass and phenology. QTL associated with seed weight and phenology mapped near previously reported QTL. The above findings provide a possibility for marker assisted breeding using markers tightly linked to photosynthate remobilization.